Analysis of 3 kW Solar Power Plant Production Optimization by Improving Energy Production Efficiency Using 3d Pvsyst Simulation Method - Fiqri, Teguh Mohammad; Yacoub, Redi Ratiandi; Kurnianto, Rudi; Rusman, Rusman; Hasan, Hasan (Faculty of Engineering, Universitas Tanjungpura, 2025)
This study aims to analyze the effect of optimizing the position of solar panels on improving energy production efficiency in a 3 kW solar power plant (PLTS) system. The 3D PVsyst simulation method was used to model the system and predict performance before and after optimization. Simulation results indicate that repositioning the solar panels can increase energy production by 2% (from 0.99 kWh to 1.01 kWh). A comparison between simulation results and actual data shows reasonably good agreement, although some differences require further investigation. Discrepancies between simulation and actual data may be attributed to several factors, such as weather conditions, component efficiency, and other environmental factors. This study concludes that optimizing the position of solar panels is an effective step to enhance the performance of PLTS systems. However, further research is needed to consider additional factors affecting system performance and to develop more accurate simulation models